New South Wales annual vaccine-preventable disease report, 2013 - Rosewell, Alexander; Spokes, Paula J; Gilmour, Robin E (Western Pacific Surveillance and Response, 2015)
Abstract: Aim: To describe the epidemiology of selected vaccine-preventable diseases in NSW for 2013. Methods: Data from the NSW Notifiable Conditions Information Management System were analysed by: local health district of residence, age, Aboriginality, vaccination status, and organism, where available. Risk factor and vaccination status data were collected for case-patients by public health units following notification under the NSW Public Health Act 2010. Results: Pertussis notification rates in infants were low and no infant pertussis deaths were reported. Despite a high number of imported measles cases, there was limited secondary transmission. The invasive meningococcal disease notification rate declined and disease due to serogroup C remained low and stable. Conclusion: Vaccine preventable diseases were relatively well controlled in NSW in 2013, with declining or stable notification rates in most diseases compared with the previous year.